Zinc Therapy in Dermatology: A Review and Update - Eliz Aryal; Elisa Bhattarai; Sabina Bhattarai (Nepal Journal of Dermatology, Venereology & Leprology)
Zinc  is  a micronutrient used over the years for many  dermatological conditions such as infections, inflammatory dermatoses, pigmentary disorders, neoplasias etc. It is used in both elemental as well as salt form, either in topical or in oral form as a therapy. An average adult weighing 70 kg has a body zinc content of 1.4–2.3 gm. The role of zinc in deficiency disorder like acrodermatitis enteropathica is already established and used widely as treatment.  Zinc has been identified as effective in the treatment of various disorders but it cannot be used as the replacement for proven first line treatment.  Zinc can be used as adjuvant therapy in many dermatological disorders. This is a narrative review where various use of zinc as therapy in dermatological disorders is highlighted.